Using Green Solvents for Phase Inversion of PVDF/TiO2 Hybrid Coatings for Gas Phase Photocatalysis - Ewoud Cosaert; Hadis Mortazavi Milani; Geraldine J. Heynderickx; Dirk Poelman (Molecules)
Long-time exposure to volatile organic compounds (VOCs) in the atmosphere can have negative health effects on humans and other living organisms. In order to purify ambient air, these VOCs can be degraded using photocatalysis. In this research, commercially available TiO2 nanoparticles were immobilized in a porous poly(vinylidene fluoride-co-hexa-fluoropropylene) (PVDF) polymer matrix, synthesized using the phase inversion method. The most used solvent for PVDF is N-methyl-2-pyrrolidone (NMP). However, this solvent is known to be harmful to humans and the environment, and there is a need to replace NMP with a more ecological ‘green’ solvent. Here, triethyl phosphate (TEP), methyl-5-(dimethylamino)-2-methyl-5-oxopentanoate (Rhodiasolv® PolarClean) and propylene carbonate (PC) were used to dissolve PVDF for the phase inversion synthesis of porous photocatalytically active PVDF/TiO2 hybrid layers onto aluminium slides. The photocatalytic degradation under UV (365 nm) of gaseous ethanol in an argon/oxygen (Ar/O2) atmosphere shows that these solvents are suitable replacements for NMP, but optimization is required to improve the performance of the layers. Apart from changing the solvent for PVDF, the UV and photocatalysis stability of PVDF has been determined, as well as the repeatability of the photocatalytic reaction, to prove that PVDF is a suitable polymer for this application.